Impact of serious mental illness on the treatment and mortality of older patients with locoregional high‐grade (nonmetastatic) prostate cancer: retrospective cohort analysis of 49 985 SEER‐Medicare patients diagnosed between 2006 and 2013. (3rd April 2019) - Fried, Dennis A.; Sadeghi‐Nejad, Hossein; Gu, Dian; Zhou, Shouhao; He, Weiguo; Giordano, Sharon H.; Pentakota, Sri Ram; Demissie, Kitaw; Helmer, Drew; Shen, Chan
Abstract: Background: The influence of serious mental illness (SMI) on the treatment and survival of patients with high‐grade prostate cancer is not well understood. We compared the initial cancer treatment and cancer‐specific mortality of SEER‐Medicare patients with locoregional high‐grade (nonmetastatic) prostate cancer with and without preexisting SMI. Methods: We identified SEER‐Medicare patients who were 67 years of age or older diagnosed between 2006 and 2013 with locoregional high‐grade (nonmetastatic) prostate cancer. Preexisting SMI was identified by claims indicative of bipolar disorder, schizophrenia, and other psychotic disorder, during the 2 years before cancer diagnosis. We used multivariable binary logistic regression to examine associations between SMI and receipt of surgery or radiation concurrent with hormone therapy (definitive initial treatment) within 1 year after cancer diagnosis. We used Kaplan‐Meier survival curves, as well as Cox proportional hazards and competing risk models to evaluate unadjusted and adjusted associations between SMI and 5‐year cancer‐specific survival. Results: Among 49 985 patients with locoregional high‐grade (nonmetastatic) prostate cancer, 523 (1.1%) had SMI and 49 462 (98.9%) had no SMI. Overall, SMI was associated with reduced odds of receiving surgery (OR = 0.66, 95% CI: 0.49‐0.89) or radiation concurrent with hormone therapy (OR = 0.81, 95% CI: 0.67‐0.98) as initial treatments in the year after cancer diagnosis. Additionally, SMI was associated with higher hazard of 5‐year cancer‐specific death (HR = 1.41, 95% CI: 1.06‐1.89) after accounting for competing risks of non‐cancer death. Conclusion: Among SEER‐Medicare patients with locoregional high‐grade (nonmetastatic) prostate cancer, those with preexisting SMI—relative to those without these conditions—were less likely to receive definitive initial treatment in the year after diagnosis and had poorer cancer‐specific survival 5 years after diagnosis. Abstract : Among older SEER‐Medicare patients with locoregional high‐grade prostate cancer, those with serious mental illness were less likely than those without serious mental illness to receive definitive initial cancer treatment within 1 year after diagnosis and had higher cancer‐specific mortality 5 years after diagnosis.